MANAJEMEN OLAH GERAK KAPAL PADA ALUR PELAYARAN SEMPIT MUSAFFAH CHANNEL DI KAPAL MV. ADNOC 223 - Sibali, Alwi; Hardiyono, Hardiyono; Sino, Hendy William (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
This research investigates the influence of ship maneuvering management on the efficiency and safety of shipping operations in the Musaffah Channel, a narrow and strategic shipping lane. Using quantitative and qualitative methods, this study collected data from direct observations and in-depth interviews with MV crew members. Adnoc 223. The research results show that complex channel conditions require careful maneuver management to avoid incidents, optimize fuel consumption and maintain appropriate sailing schedules. Data analysis reveals that adaptive speed and precise maneuvering contribute significantly to shipping safety and efficiency. This research provides valuable insight into the importance of integration between navigational expertise and advanced technology in ship maneuvering management, and highlights the importance of training and proactive strategies in dealing with the challenges of navigation in narrow channels. The implications of these results are very relevant for operational management and business strategy in the shipping industry, showing that the success of maneuver management directly influences the sustainability and competitive advantage of shipping companies.